Influence of Job Fit, Perceived Support, and Organizational Identification in the Sales Force: An Analysis of Antecedents and Outcomes - DeConinck, Jim; DeConinck, Mary Beth; Lockwood, Frank (Archives of Business Research, 2015)
Abstract Controlling turnover is an important issue for all organizations. But, the situation is especially relevant for professional salespeople where turnover and the costs associated with replacing salespeople are both high. While previous research has examined antecedents related to salesforce turnover, sparse research exists examining how the level of support salespeople perceive they receive from their sales manager and the organization are related to their intention to leave. In addition, the degree to which salespersons identity and fit with the organization’s goals and values also have been studied infrequently. The results indicate that perceived support, job fit, and organizational identification are important variables related to salesforce turnover.